Jewish Cult and Hellenistic Culture : Essays on the Jewish Encounter with Hellenism and Roman Rule - Collins, John J. (Brill Book Archive Part 1, ISBN: 9789004472495., 2005)
This is a collection of 12 essays, written since 1997, on themes related to Hellenistic (Greek-speaking) Judaism. They include a review essay on recent scholarship on Hellenistic Judaism, a discussion of the question of anti-Semitism in antiquity, a study of the Hellenistic reform in Jerusalem, several studies of individual texts and an essay on the circumstances that led to the first Jewish revolt against Rome.